An UHPLC-MS/MS Method for Target Profiling of Stress-Related Phytohormones - Novák, Ondřej; Floková, Kristýna (Methods in molecular biology, 2018)
The methodology described here represents an improved strategy for analysis of a broad range of stress-related plant hormones including jasmonates, salicylic acid, abscisic acid, and auxin metabolites. The method conditions are optimized in order to reduce the background effect of complicated plant matrix, allow effective preconcentration and thus perform highly sensitive profiling of multiple plant hormones by ultrahigh performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS).
Keywords: cyklopentany; Salicylic Acid; vysokoúčinná kapalinová chromatografie; Oxylipins; Abscisic Acid; Indoleacetic Acids; Chromatography, High Pressure Liquid; regulátory růstu rostlin; Cyclopentanes; tandemová hmotnostní spektrometrie; kyselina abscisová; kyseliny indoloctové; oxylipiny; kyselina salicylová; Plant Growth Regulators; Tandem Mass Spectrometry